The Electrochemical Behavior of Carbon Steel Wires of Nepal in Different Environments - Bhattarai, Jagadish (Journal of Nepal Chemical Society, 2009)
The electrochemical behavior of carbon steel wires of Nepal is studied in 1 M HCl, 0.5 M NaCl and 1 M NaOH solutions at 25°C, open to air using immersion tests and electrochemical measurements. The corrosion rates of the carbon steel wires were found to be about 20-50 mm/y in acidic 1 M HCl and 0.1-0.2 mm/y in neutral 0.5 M NaCl. The corrosion rate of all the examined steel wires in alkaline 1 M NaOH solution (that is, 7 - 18 x 10-3 mm/y) was found nearly three orders of magnitude lower corrosion resistance than in 1 M HCl solution at 25°C, mostly due to an ennoblement of the open circuit potentials of the steel wires at passive potential regions (that is, -200 to 250 mV vs SCE) in 1 M NaOH solution. The steel wires seem to be very corrosion resistance materials in very alkaline environments like cement-based materials. Keywords: Carbon steel wire; Corrosion tests; Polarization measurement; HCl;  NaCl and NaOH solutionsDOI: 10.3126/jncs.v24i0.2388Journal of Nepal Chemical Society Vol. 24, 2009 Page: 31-38